Respon Pertumbuhan Pakcoy (Brassica rapa L. var. chinensis) Terhadap Variasi Komposisi Media Tanam - Ningtyas, Dewi Nurma Yanti (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2026)
The growth of bok choy (Brassica rapa L. var. chinensis) is affected by the type and composition of growing media. This study evaluated the growth response of pakcoy to five media combinations: P1: Soil + Rice Husk Charcoal (2:1), P2: Soil + Rice Husk Charcoal + Cow Manure Compost (2:1:1), P3: Soil + Rice Husk Charcoal + Cocopeat (2:1:1), P4: Soil + Rice Husk Charcoal + Vermicompost (2:1:1), and P5: Soil + Cow Manure Compost + Vermiculite + Malang Sand (2:1:1:1). Growth was assessed based on plant height, leaf number, root length, shoot fresh weight, and root fresh weight. The data were subjected to analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level (α = 0.05). The results indicated that media composition significantly affected all growth parameters. Among the treatments, P4 produced the most favorable growth response, recording a plant height of 22.33 cm, 12 leaves, a root length of 50.83 cm, a shoot fresh weight of 31.00 g, and a root fresh weight of 25.42 g. Higher growth observed under P4 was likely associated with the role of rice husk charcoal through improved aeration and porosity, while vermicompost supplied essential nutrients and enhanced beneficial microbial activity, thereby creating more favorable growing conditions for bok choy compared with the other treatments.